Splenic infarction in alcoholic hepatitis - Aijazi, Muaz (Proc (Bayl Univ Med Cent), 2020)
Splenic infarctions have been reported in cirrhotic patients with comorbidities (e.g., primary biliary cirrhosis), but there is little to no mention of spontaneous splenic infarction in alcoholic hepatitis. This condition is notable, as splenic function has been shown to decrease in alcoholic liver disease, but the exact pathophysiology has been unclear. We describe a relatively young cirrhotic woman who developed splenic infarctions in the setting of alcoholic hepatitis.